A review of mental health literacy strategy for adolescence - Padmi Dhyah Yulianti; Endang R. Surjaningrum (Intelektual Pustaka Media Utama, 2021)
Adolescents' problems concerning mental health could a burden for individual, families, and environments. To prevent further worsening mental problems, mental health literacy is needed. Mental health literacy has been promoted in advanced countries. However, it is implemented optimally in developing countries. This research aimed to find out the mental health literacy strategies done by adolescents. This article is a systematic literature review study. To obtain the articles for analysis purposes, search engine assistance was used such as Cochrane Library, Medpub, and ERIC. From 82 collected articles, and inclusion and exclusion stages were carried out to select the articles for the literature study purpose. They were then extracted from individually to get the significant findings. From the results of 11 reviewed articles, a conclusion was found. There were different mental health literacy implementation strategies in each country. Various mental health strategy types for adolescents covered national, community, school-based, and self-empowerment scope strategies.